Barriers and opportunities to innovation in the Malaysian Army: a multilevel approach: A MULTILEVEL APPROACH - Armawai, Mohd Aman; Abidin, Imaduddin; Muhamad Tamyez, Puteri Fadzline (Vojnotehnički glasnik / Military Technical Courier, 2025)
The objective of the present study is to examine the barriers and opportunities to innovation at the individual, team, and organisational levels in the Malaysian Army. This exploratory study uses an interpretative phenomenology approach to analyse qualitative data from 15 interviews conducted with military officers and other ranks who contributed consistently to the Malaysian Armed Forces’ innovations. Findings highlighted that individual-level barriers were subdivided into seven themes, while team-level barriers consist of six and organisational-level barriers are four themes. This study recommends the roles of various actors and teams within the innovation ecosystem in removing barriers to innovation. The present study's findings contribute to a more holistic understanding of barriers to innovation, which is an under-researched topic in the Malaysian Army. This study offers a multilevel framework of barriers and potential interventions for the Malaysian Army to support innovation by addressing unique challenges and suggesting avenues for further research
Keywords: innovation; barriers to innovation; ecosystem; armed forces; military; malaysian Army